Bone marrow infiltration by Non-Hodgkin lymphoma: An experience in a tertiary care centre - Suhail, Maymoona; Asad Mahmood; Rafia Mahmood; Saima Zahir; Syeda Samia Shafaat; Sumaira Illyas (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the frequency and patterns of bone marrow infiltration in non-Hodgkin lymphoma patients. Method: The cross-sectional study was conducted at the Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from April to October 2021, and comprised patients of either gender aged 20-80 years who had been diagnosed with non-Hodgkin lymphoma. Following assessment and as per standard protocol, bone marrow aspirate and trephine biopsy were done on all patients from the posterior superior iliac spine, and slides were prepared and assessed. Data was analysed using SPSS 25. Results: Of the 100 patients, 67(67%) were males and 33(33%) were females. The overall mean age was 54.99+12 years, and mean duration of symptoms was 11.7±1.5 months. Diffuse large B-cell lymphoma was the commonest type 43(43%). Infiltration of marrow occurred in 38(38%) patients, with 12(12%) of them being cases of mantle cell lymphoma. The commonest infiltration pattern was diffuse in 17(17%) cases, followed by focal/nodular in 10(10%). Conclusion: Diffuse large B-cell lymphoma was found to be the commonest type of non-Hodgkin lymphoma, and marrow infiltration occurred most frequently in cases of mantle cell lymphoma. Key Words: Bone marrow, Infiltration, Non-Hodgkin lymphoma.